INTERPRETATION OF DEDICATION IN THE EPIC “LISON UT-TAIR” - Jumaev Rashid Normurotovich (Western European Studies, 2024)
The article analyzes the concept of diligence and diligence in the work of the great thinker and mystic poet Alisher Navoi, in particular in his works “Saddi Iskandari”, “Mahbub ul-Qulub” and “Lison ut-Tayr” as a high human virtue and mystical revolution. The essence of the concept of bravery, diligence, nobleness is that which is directly related to the highest human qualities such as love and generosity, and it also includes the inner strength, enthusiasm and courage of a person, mental and spiritual maturity, confidence and faith, clearly reflecting the value, is shown on the basis of a number of examples
Keywords: epic; poet; tariqat; love